Morphometry of proximal femur in South Indian Population - Resmi George; Nithin K Raju (Asian Journal of Medical Sciences, 2024)
Background: Proximal femur analysis plays a vital role in orthopedic surgery, implant design, fracture care, and research. Studying this complex bone helps surgeons select the right implants, plan fracture treatment, and understand bone strength. This growing field improves clinical outcomes and enhances scientific knowledge. Our study analyzes the morphometry of proximal femur, particularly the head and neck, to further explore its implications. Aims and Objectives: To study the morphometric measurements of the proximal end of the femur quantitatively in the South Indian population from the dry femora available in the Department of Anatomy, Government Medical College, Kottayam. Materials and Methods: This cross-sectional study was conducted in 101 dry femora available in the Department of Anatomy, Government Medical College, Kottayam. The measurements were taken with digital Vernier calipers and a goniometer. All continuous variables were expressed as mean with standard deviation. Statistical differences between the right and left sides were analyzed with Student’s independent sample t-test (for parametric variables) and Mann–Whitney U test (for non-parametric variables). Results: The mean vertical and anteroposterior diameter of the femoral head, superior and inferior length of the femoral head, the anteroposterior and vertical diameter of the femoral neck, superior and inferior lengths of the femoral neck, neck-shaft angle, and intertrochanteric length were 39.61±3.29 mm, 40.17±3.14 mm, 33.01±3.6 mm, 23.88±4.32 mm, 24.22±3 mm, 29.59±3 mm, 21.75±3.81 mm, 32.03±5.58 mm, 124.11±6.37, 60.31±7.33 mm, respectively. There was a statistically significant difference in the mean of neck anteroposterior diameter and neck-shaft angle between the right and left sides where the left side had the higher value. Conclusion: Notable skeletal metric variations exist amidst different populations. Proximal femoral dimensions can be acquired through either manual means or radiological information. These measurements can be used in designing orthopedic implants for the South Indian population.